Extreme Testing of Guard Cables with Fiber Optics: A Case Study - González-Barbosa, Erick-Alejandro; Jurado-Pérez, Fernando; Gonazlez-Barbosa, Jose-Joel; Méndez-Gutiérrez, Julio Cesar (Ingeniería, 2024)
Context: Optical fiber ground wires (OPGWs) sometimes melt and rupture when exposed to extreme conditions, such as atmospheric discharges, short circuits, and corrosive agents, that affect their electrical and mechanical properties. These conditions depend on the geographical area where the cable is installed, with the most critical being industrial and coastal zones as well as marine and mountainous environments. This research analyzes a cable rupture due to lightning strikes from a coastal zone. Method: The analysis discusses cable selection criteria based on engineering specifications. It also discusses standardized test methods and procedures. The tests performed are based on visual and dimensional inspections, mechanical stress assessments, and chemical analysis. Results: The complete analysis allows determining the necessary basis for the characterization and mathematical parameterization of OPGWs, establishing considerations that contribute to proper functioning in order to reduce communication and power supply interruptions. Conclusions: This study helps to estimate the behavior of the entire structure and the quality of failed OPGWs, providing insights into improving cable design and maintenance practices in harsh environments.